MEDIA GAMBAR MENINGKATKAN KEMAMPUAN MENULIS - Siti Mukayah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
This research uses classroom action research model, hence method used by writer is technique of data collecting research which writer use that is 1) observation technique 2)test technique 3)interview technique. Cycle I only a few students who answer questions asked by other teacer or students, while in clycle il many students who dare to answer questions, although theanswers ar not necessarily true. From the result of this study can be concluded as follows writing poetry by using the image media can achieve mastery of cognitive learning outmes and life skills